Utilization Of Openkm In The Context Of Iterative Process Automation - Baghiroh, Raeh Niken; Haroky, Faruq (Jurnal Ilmiah Mandala Education (JIME), 2021)
This study aims to implement a management management system in a vocational high school in Pandeglang. The literature used as the basis for research is knowledge management, personal knowledge management. The research approach used is an action research approach, because the researcher wants to show changes before and before implementing the action. The results of this study indicate the benefits of using OpenKM in schools that are the object of research.